The implementation of independent curriculum at senior high schools: English teachers’ perspectives - Edy Waloyo; Vina Alfu Magfiroh; Amroh Umaemah (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2023)
In Indonesia, the independent curriculum meets the requirements and desires of a wide range of students, providing an alternative to the government-mandated curriculum without sacrificing educational quality or preparing students for careers or post-secondary education both locally and abroad. The purpose of this research was to explore English teachers’ perspectives related to the independent curriculum, its implementation, and its challenges at one of the senior high schools in Cirebon City. This research used a case study approach with qualitative methods and the subjects were two English teachers who taught English with the independent curriculum. Observation, interviews, and documentation were used to collect the data. The results show that regarding the implementation of the independent curriculum, English teachers give their positive (29.2%), negative (29.2%), neutral (33.3%), and unclear (8.3%) perspectives. The Implementation of the independent curriculum in learning English is carried out by strengthening the Pancasila student profile project and learning. The implementation of learning English includes three stages: planning, implementing, and evaluating. However, there are several challenges, such as a lack of student motivation and the poor mindset of students towards English.Keywords: independent curriculum, implementation, teachers’ challenges.